Martin Luther King and Black Rights (Journal of the College of Basic Education, 2022)
We cannot talk about black Americans of color and the persecution and atrocities they have been subjected to in the United States of America without addressing Martin Luther King, a fighter, revolutionary preacher, and black social reformer. With white citizens, he carried the banner of the struggle against American racism and those calling for an end to racial discrimination against blacks. He was famous for his peaceful struggle for black Americans to obtain their political and civil rights. Martin Luther King considered one of the most important figures who fought for freedom and human rights. Luther founded the Southern Christian Leadership, a movement aimed at obtaining equal civil rights for African Americans. King refused violence of all kinds, was awarded the Nobel Peace Prize and was the youngest to receive it. He was assassinated on April 4, 1968, and became a victim of his peaceful cause